Authentic Material and Automaticity for Teaching English - Widyastuti Widyastuti (IAIN Salatiga, 2017)
This article discusses how to make students of Science Education in first year feel interesting in English lesson, understanding the text well and can communicate English fluency. It has been suggested that Authentic Material and Automaticity Theory not only creates a friendly and fun condition in teaching reading but helps students to study comprehensibly so they are able to understand the text, structure, vocabulary easily, read fluently and they also can communicate in English. The authentic material can make the teaching learning process fun and eliminate boring because the topics and materials can be found in internet so it will be more visually and interactive . Automaticity theory can solve the problem of students who must memorize words that make them feel boring and forget the words soon. The other benefit is the students can exposure the real language being used in a real context and stimulate studens’idea, encouarage them to relate themselves with real-life experiencesThese strategies can make the students understand easily and enjoy the teaching learning process. By combining authentic material and automaticity strategies for teaching English in science education, will develop readers (students) to become fully competent and fluent.